2015
DOI: 10.2135/cropsci2015.02.0090
|View full text |Cite
|
Sign up to set email alerts
|

Grazing Management Affects Establishment Performance of Rhizoma Peanut Strip Planted into Bahiagrass Pasture

Abstract: Abbreviations: RP, rhizoma peanut; RS-28, rotational stocking with a 28-day rest period; RS-42, rotational stocking with a 42-d rest period; Y1, year of planting; Y2, year after planting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…In this study, the first six seasons up to the winter 2013, the brachiaria grass showed similar response as in monoculture. In those seasons, the forage peanut contributed a lower proportion in the botanical composition (Figure ) because it presents a slow establishment (Cassal, Garcia, & Monks, ; Castillo et al., ). From the spring of 2013, the forage peanut showed an increment in the botanical composition in canopies with lower light competition (10 and 20 cm).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the first six seasons up to the winter 2013, the brachiaria grass showed similar response as in monoculture. In those seasons, the forage peanut contributed a lower proportion in the botanical composition (Figure ) because it presents a slow establishment (Cassal, Garcia, & Monks, ; Castillo et al., ). From the spring of 2013, the forage peanut showed an increment in the botanical composition in canopies with lower light competition (10 and 20 cm).…”
Section: Discussionmentioning
confidence: 99%
“…Rhizoma peanut has a high potential for increasing soil N supply and improving litter quality in C4 grass pastures (Cathey, Sinclair, & Mackowiak, 2013). It can be grown in monoculture for hay or in combination with perennial grasses for grazing systems (Castillo et al, 2015). Similar to many other legume species, RP largely relies on its rhizobium symbionts for biological nitrogen fixation (BNF), which is a primary source of nitrogen (N) in agricultural systems Tg N annually, Herridge, Peoples, Boddey, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, we can highlight two forms of growth: crown former and stolon former. There is also legume rhizome‐former growth, such as Arachis glabrata with promising results in studies mainly in the south of the USA (Castillo et al., 2015; Dubeux, Blount, et al, 2017; Mullenix et al., 2016). However, A. glabrata is so far little used in Brazil.…”
Section: Forage Legume Management In Tropical Pasturesmentioning
confidence: 99%